Cartographie De L’état Du Couvert Végétal Du Nord De La Côte D’ivoire À Partir D’images Satellites: Exemple De La Zone De Korhogo - StéphaneKoff, Avy; Fora, Abderrahman Ait; Elbelrhiti, Hicham (European Scientific Journal, ESJ, 2016)
The purpose of this study is to determine the state of the vegetation cover in the region of Korhogo through remote sensing. Nowadays, the problem of desertification in the Sahel is serious. This could be explained by the phenomenon of climate change. We want to map the state of the vegetation cover in the study area. This study therefore focuses on the state of the vegetation cover in the region of Korhogo in northern Côte d’Ivoire. We will use one Landsat satellite image from December 16th 2000 and proceed with image processing. Processing techniques by the normalized difference vegetation index, the index armor and colorful composition 472. After these treatments in our pictures, we observe the behavior of vegetation. We can then get an overview of the vegetation in this area.